Risk of Seizure Recurrence with Neurocysticercosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
The risk of seizure recurrence after a first seizure due to neurocysticercosis (NC) was evaluated in a prospective study of 77 patients at the School of Medicine and Research Institute, University of Cuenca, Ecuador, and Columbia University, New York.